Proposed Business Model of Dairy Cooperative to Empower Dairy Supply Chain of Dairy Cooperative - Nuryadi, Rizka Tauria; Mulyono, Nur Budi (The Asian Journal of Technology Management (AJTM), 2019)
Abstract. Huge number of small dairy farmers dispersed in wide are of West Java Indonesia had become a major contributor of fresh-milk production. Dairy-cooperative plays important role in collecting fresh-milk from dairy farmer, conduct pre-processing, and sell fresh milk to large industry and end customers. Some dairy cooperative further process fresh milk into dairy products. The role of dairy cooperative is central to improve the competitiveness of the dairy farmers against others fresh milk producer. This research aims to understand in dairy supply chain especially situation faced by dairy farmer and dairy-cooperative, and to provide recommendation on the new business model for dairy cooperative to empower themselves and improve competitiveness of the dairy farmers. We employ secondary data analysis to understand the situation in the upstream of the dairy supply chain and conjoint analysis to get customer preference as a basis for new business model development for dairy cooperative. Our result suggests that dairy cooperative must proactively collaborate with the owner of an abandon land for seeding forage pasture for the upstream strategy, and focusing value proposition in packaging, local brand, and dairy farmers assistance.Keywords: Dairy cooperative, empowerment, policy, small dairy farmers, supply chain